Stable isotopes of oxygen reveal dispersal patterns of the South American sea lion in the southwestern Atlantic Ocean. (16th July 2013) - Zenteno, L.; Crespo, E.; Goodall, N.; Aguilar, A.; de Oliveira, L.; Drago, M.; Secchi, E. R.; Garcia, N.; Cardona, L.
Abstract: Stable isotopes of oxygen have been widely used to reconstruct paleotemperatures and to investigate the thermal environment of fishes and mollusks, but they have only occasionally been used as geographical markers in marine systems. As bone apatite grows at a constant temperature in marine mammals and food is the major source of water for these animals, particularly for pinnipeds, variations in the ratio of stable isotopes of oxygen ( δ 18 O) of bone apatite will likely reflect changes in the δ 18 O values of diet, and thus of the surrounding water mass, despite the potential confounding role of factors as the proximate composition of diet, sex and body size. Here, we used the δ 18 O values in bone apatite to investigate whether adult males of South American sea lion ( Otaria byronia ), from three regions in southwestern Atlantic Ocean (Brazil, Patagonia and Tierra del Fuego in Argentina), used the same water masses to forage and whether differences exist in the water masses used by sea lions differing according to sex and developmental stage. Statistically significant differences were observed among the δ 18 Obone values of adult males from the three regions, with those from Patagonia more enriched in 18 O, as expected from the δ 18 Oseawater values. These results revealed restricted dispersal movements of adult males between the three areas. On the other hand, adult males and females from Patagonia did not differ in average δ 18 Obone values, thus indicating the use of foraging grounds within the same water mass. Finally, the variability in the δ 18 Obone values of young of both sexes was much wider than the adults of the same sex from the same region, which suggests the existence of a juvenile dispersal phase in both sexes, although much shorter in females than in males. These results confirm the usefulness of stable isotopes of oxygen as habitats tracers in marine mammals.